Revelation of the Excellent Intrinsic Activity of MoS2|NiS|MoO3 Nanowires for Hydrogen Evolution Reaction in Alkaline Medium - Wang, Chuanqin; Tian, Bin; Wu, Mei; Wang, Jiahai (ACS applied materials & interfaces, 2017)
Loading an electrocatalyst on poorly conducting substrate can easily lead to undervaluation of its intrinsic property. In this study, the excellent activity of MoS2|NiS|MoO3 nanowires for hydrogen evolution is revealed. The precursor NiMoO4 synthesized on chemically polished Ti foil can be successfully converted to MoS2|NiS|MoO3 catalyst via gas-phase sulfurization. Without deep polish in sulfuric acid for 2 h, the as-synthesized materials do not show competitive results. After sulfurization, the surface morphology of the precursor is transformed into rough features, and the peripheries of these electrocatalysts are coated by multilayered and misaligned MoS2 with a high density of active sites and conductive component NiS. Further analysis shows that defect MoO3 is embedded inside each nanowire, which may facilitate fast electron transfer. Such nanostructured architecture shows promising results for hydrogen evolution reaction in alkaline medium with only 91 mV overpotential for the current density of 10 mA cm–2 and robust long-term stability during more than 20 h of tests.